Breaking free from the trend: outlier policies promote sustainable poultry practices - Khire, Ishan; Ryba, Ren (Frontiers in Animal Science, 2025)
The intensification of livestock production is globally on the rise, driven by increased demand and urbanization. This presents a large potential threat to animal welfare, environmental sustainability, and public health, particularly in the developing world where the increase in intensification is most prominent. However, it remains unclear whether policymakers have tools to limit intensification even as their country or state increases in wealth. In this paper, we address the knowledge gap: is it possible for countries or states to develop economically while keeping livestock intensification low? We test whether there exist any jurisdictions that have maintained unexpectedly low levels of livestock intensification, after statistically accounting for wealth and other demographic and agricultural variables. Using India’s egg and chicken meat industry as a case study due to its immense size and its intermediate stage of economic development, we successfully identify a number of states that have developed economically while maintaining low levels of chicken intensification. Subjecting these Northeastern states to a deeper examination, we find that these states have deliberately pursued policies prioritizing organic agriculture and environmentally sustainable methods of production. While there are hurdles and limitations to implementing these organic policies, the examined jurisdictions offer promise for policymakers seeking to keep levels of intensification low and maintain good animal welfare as countries develop.